1994
DOI: 10.1152/ajpcell.1994.267.5.c1501
|View full text |Cite
|
Sign up to set email alerts
|

Activation of recombinant trp by thapsigargin in Sf9 insect cells

Abstract: The mammalian protein responsible for Ca2+ release-activated current (Icrac) may be homologous to the Drosophila protein designated trp. Thus the activity of trp, and another Drosophila protein designated trp-like or trpl, may be linked to depletion of the internal Ca2+ store via the so-called capacitative Ca2+ entry mechanism. To test this hypothesis, the effect of thapsigargin, a selective inhibitor of the endoplasmic reticulum Ca2+ pump, on trp- and trpl-induced whole cell membrane current was determined us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
196
1
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(207 citation statements)
references
References 13 publications
9
196
1
1
Order By: Relevance
“…Comparing the endogenous insect SOC channels with expressed trp channels in Sf9 cells, Vaca et al [29] showed that this SOC channel and the trp channel were clearly different regarding the permeation properties of Ca 2+, Ba 2+, Mg 2+, and Na +. Different permeation properties were also reported for store operated channels in a human epidermal cancer cell line (A431) [20], in vascular endothelium [28], in HT29 colonic carcinoma cells [16], and in MDCK cells [4]. Selectivity and permeation properties have so far been proven the best tools to distinguish different members of the SOC family.…”
Section: Discussionmentioning
confidence: 97%
“…Comparing the endogenous insect SOC channels with expressed trp channels in Sf9 cells, Vaca et al [29] showed that this SOC channel and the trp channel were clearly different regarding the permeation properties of Ca 2+, Ba 2+, Mg 2+, and Na +. Different permeation properties were also reported for store operated channels in a human epidermal cancer cell line (A431) [20], in vascular endothelium [28], in HT29 colonic carcinoma cells [16], and in MDCK cells [4]. Selectivity and permeation properties have so far been proven the best tools to distinguish different members of the SOC family.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, although the two Drosophila trp proteins are most related among the four, the functional roles of trp and trpl in Drosophila phototransduction are thought to be different [6,20]. When expressed in Sf9 cells, the Drosophila trp was activated by store depletion whereas the Drosophila trpl was not and channels formed by these two proteins also had different ion selectivities [10,11]. Part of these differences may result from the fact that at the C-terminus of the Drosophila trp, there is a 9-fold repeat of a very hydrophilic eight amino acid sequence (DKDKKPGD), which does not occur in trpl and the other two trp homologues which have shorter C-terminal tails.…”
Section: Discussionmentioning
confidence: 99%
“…4a) trp or trpl, the expressed protein was found to form Ca 2÷ permeant channels that functions in the IPJCa 2+ signaling pathway [10][11][12][13]. Therefore, it is reasonable to assume that the human trp may also play a role in the IPJCa 2+ signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations